Unsaturated polyester resin composite material and preparation method thereof
By using composite thermal fillers and modified carboxylic styrene butadiene emulsion in unsaturated polyester resins, the problem of insufficient thermal conductivity of existing unsaturated polyester resins is solved, and higher thermal conductivity, flame retardant properties and mechanical properties are achieved, which is suitable for industrial applications under high temperature and high load conditions.
Patent Information
- Application Number
- CN202411451029.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The thermal conductivity of existing unsaturated polyester resins is insufficient, making it difficult to meet the safety and reliability needs of automobiles, electrical appliances and electronic products under high temperature and high load conditions.
Using composite thermal filler, nanoboronitride is generated in situ on the surface of expanded graphite, the thermal conductivity of expanded graphite is improved, and the fluorine-containing functional groups are introduced through the modified carboxylic styrene butadiene emulsion to enhance the aging resistance of unsaturated polyester resin composites.
It significantly improves the thermal conductivity and flame retardant properties of unsaturated polyester resin composite materials, while enhancing its mechanical properties and aging resistance, which can better meet the needs of industrial applications.
Smart Images

Figure BDA0005089129700000121 
Figure BDA0005089129700000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester resin material preparation, and in particular to an unsaturated polyester resin composite material and a preparation method thereof. Background Art
[0002] Unsaturated polyester resin is generally a linear polymer compound with ester bonds and unsaturated double bonds formed by the polycondensation of unsaturated dibasic acid diols or saturated dibasic acid unsaturated diols. Usually, the polyesterification polycondensation reaction is carried out at 190°C to 220°C until the expected acid value (or viscosity) is reached. After the polyesterification polycondensation reaction is completed, a certain amount of vinyl monomer is added while hot to form a viscous liquid. Such a polymer solution is called unsaturated polyester resin, which is an important thermosetting resin variety in the development of modern plastics industry.
[0003] Unsaturated polyester resins play an important role in all walks of life, especially in the manufacturing of automobile, electrical and electronic product parts. With the advancement of science and technology and the improvement of people's living standards, the market demand for automobiles, electrical and electronic products continues to increase, and these products have higher and higher performance requirements for materials during use. For example, automobile parts not only need to have good mechanical strength, but also excellent heat resistance and flame resistance to ensure safety and reliability under high temperature and high load conditions; at the same time, the shell and internal structure of electronic products also require materials to have good dimensional stability to cope with deformation problems caused by temperature changes.
[0004] Therefore, improving the thermal conductivity of unsaturated polyester resin has become one of the important directions for future material research and development. The current modification methods include introducing fillers, modifiers and other comonomers with thermal conductivity to improve the thermal conductivity of the resin; in addition, the development of new curing agents and cross-linking agents is also an important way to improve its thermal conductivity. Through the application of these technical means, the performance of unsaturated polyester resin will be further improved to meet more stringent industrial application requirements.
[0005] For example, Chinese patent document CN201711488922.1 discloses a modified unsaturated polyester resin, and the raw materials for preparing the modified unsaturated polyester resin include maleic anhydride and phthalic anhydride as acid raw materials; propylene glycol, diethylene glycol and trimethylolpropane as alcohol raw materials; wherein the alcohol-acid ratio is 1:(1-1.2), and the molar ratio of the total molar amount of propylene glycol and diethylene glycol to the molar ratio of trimethylol is (0.75-0.95):0.1; it also includes styrene, α-methylstyrene and an inhibitor, the amount of styrene is 30%-33% of the total mass of the acid raw material and the alcohol raw material, the amount of α-methylstyrene is 2%-6% of the total mass of the acid raw material and the alcohol raw material, and the inhibitor is 0.01-0.05%; at the same time, a preparation method of the modified unsaturated polyester resin is also disclosed, which can improve the toughness of the unsaturated polyester resin, avoid cracking and deformation, and enhance the strength and hardness of the resin, but its thermal conductivity still needs to be further improved. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention aims to provide an unsaturated polyester resin composite material and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme:
[0008] A method for preparing an unsaturated polyester resin composite material comprises the following steps:
[0009] S1. Preparation of unsaturated polyester solution
[0010] 1,3-propylene glycol, 1,6-hexanediol, succinic acid, phthalic anhydride, maleic anhydride and catalyst monobutyl tin oxide are added into a reactor, heated and stirred at 190-220° C. in an inert atmosphere for dehydration reaction, and when the acid value of the reaction system drops to 25-30 mgKOH / g, an unsaturated polyester solution is obtained.
[0011] In this step, the mass ratio of 1,3-propylene glycol, 1,6-hexanediol, succinic acid, phthalic anhydride, maleic anhydride and monobutyl tin oxide is 15-25:10-20:10-15:10-20:15-25:0.3-0.5.
[0012] S2. Preparation of unsaturated polyester resin composite material
[0013] Add the composite thermal conductive filler and the modified carboxyl styrene butadiene emulsion to the unsaturated polyester solution prepared in step S1, stir evenly, then add the crosslinking agent, initiator and accelerator, mix evenly and degas, and cure at 120-140° C. for 2-5 hours to obtain an unsaturated polyester resin composite material.
[0014] In the technical solution of the present invention, the preparation method of the composite thermal conductive filler is as follows:
[0015] (1) immersing the expanded graphite in a boric acid solution, taking it out and drying it, and then placing it in an ammonia atmosphere for calcining to obtain an expanded graphite-loaded nano-boron nitride material;
[0016] (2) The expanded graphite-loaded nano-boron nitride material is dispersed in an ethanol aqueous solution, and then a silane coupling agent KH550 is added thereto, and the mixture is stirred for 1-3 hours. The mixture is filtered, washed, and dried to obtain a composite thermal conductive filler.
[0017] Specifically, in step (1), the mass ratio of expanded graphite to boric acid solution is 1-2:10-15, for example, 1:10, 1:12, 1:15, 1.5:10, 1.5:12, 1.5:15, 2:10, 2:15 can be selected, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] More specifically, the mass fraction of the boric acid solution is 1-3%. In some embodiments of the present invention, for example, 1%, 2%, or 3% can be selected, but it is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0019] In the technical solution of the present invention, in step (1), the process conditions for calcination are: the flow rate of ammonia is 100-200 mL / min, the calcination temperature is 450-600° C., and the calcination time is 45-60 min.
[0020] In the technical solution of the present invention, in step (2), the mass ratio of the expanded graphite-loaded nano-boron nitride material to the silane coupling agent KH550 is 10-15:1-3, for example, 10:1, 10:2, 10:3, 12:1, 12:3, 15:1, 15:2, 15:3 can be selected, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] In the technical solution of the present invention, the preparation method of the modified carboxyl styrene butadiene emulsion is as follows:
[0022] (01) adding sodium dodecyl sulfate and tert-dodecyl mercaptan to deionized water, stirring evenly, then introducing nitrogen to expel the air, then adding butadiene, 3,5-bis(trifluoromethyl)styrene, and acrylic acid, stirring and heating to 45-55° C., adding initiator ammonium persulfate, reacting for 2-5 hours, and after the reaction is completed, obtaining a carboxylated styrene butadiene latex dispersion;
[0023] (02) The carboxylated styrene butadiene latex dispersion and ethylene glycol diglycidyl ether are uniformly mixed, and heated at 70-85° C. for reaction for 2-3 hours to obtain a modified carboxylated styrene butadiene latex.
[0024] Specifically, in step (01), the mass ratio of sodium dodecyl sulfate, tert-dodecyl mercaptan, deionized water, butadiene, 3,5-bis(trifluoromethyl)styrene, acrylic acid and ammonium persulfate is 1-2:1-3:100:20-25:15-25:10-15:0.5-1.
[0025] Specifically, in step (02), the mass ratio of carboxylated styrene butadiene latex dispersion and ethylene glycol diglycidyl ether is 30-40:4-6. In some embodiments of the present invention, for example, 30:4, 30:5, 30:6, 35:4, 35:6, 40:4, 40:5, 40:6 can be selected, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In the technical solution of the present invention, the mass ratio of the unsaturated polyester solution, the composite thermal conductive filler, the modified carboxyl styrene butadiene emulsion, the crosslinking agent, the initiator and the accelerator is 40-60:15-25:30-40:10-15:0.4-0.6:0.3-0.5.
[0027] Specifically, the cross-linking agent is selected from epoxidized soybean oil acrylate.
[0028] Specifically, the initiator is selected from benzoyl peroxide, ethyl perbenzoate or dicumyl peroxide.
[0029] Specifically, the promoter is selected from cobalt naphthenate, zinc oxide or barium oxide.
[0030] The present invention also provides an unsaturated polyester resin composite material prepared by the above preparation method.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The composite thermally conductive filler provided by the present invention generates nano boron nitride in situ on the surface of expanded graphite by an in-situ generation method, thereby improving the thermal conductivity of the expanded graphite, thereby improving the thermal conductivity of the unsaturated polyester resin composite material; the expanded graphite will undergo thermal decomposition at high temperature to generate a carbon layer with good thermal insulation performance. The present invention loads nano boron nitride on the expanded graphite, which can further improve the density of the carbon layer. The expanded graphite and the nano boron nitride work together to improve the flame retardant performance of the unsaturated polyester resin composite material; then, the expanded graphite loaded nano boron nitride material is surface treated with a silane coupling agent KH550, which helps to improve the dispersibility and compatibility of the composite thermally conductive filler in the resin, thereby improving the mechanical properties of the unsaturated polyester resin composite material.
[0033] (2) The modified carboxylated styrene butadiene latex provided by the present invention adopts 3,5-bis(trifluoromethyl)styrene to replace the traditional styrene, and improves the aging resistance of the unsaturated polyester resin composite material by introducing fluorine-containing functional groups into the unsaturated polyester resin composite material; then, ethylene glycol diglycidyl ether is used to modify the carboxylated styrene butadiene latex dispersion, and the epoxy groups in the ethylene glycol diglycidyl ether react with the carboxyl groups in the carboxylated styrene butadiene latex dispersion, and the carboxyl groups are converted into ester groups, thereby improving the compatibility between the carboxylated styrene butadiene latex and the unsaturated polyester. In addition, the introduction of ethylene glycol diglycidyl ether can also improve the toughness of the unsaturated polyester resin composite material, and further improve the mechanical properties of the unsaturated polyester resin composite material.
[0034] (3) In the process of preparing the unsaturated polyester resin composite material of the present invention, through the action of the cross-linking agent, initiator and promoter, each raw material is connected to the chain segment of the unsaturated polyester through chemical bonds, which can avoid the problems of poor material consistency and comprehensive performance failing to achieve the expected effect due to simple compounding of the raw materials and mutual conflict between the raw materials. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0036] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0037] The mesh number of the expanded graphite used in the embodiment of the present invention is 400 meshes.
[0038] Example 1
[0039] A method for preparing an unsaturated polyester resin composite material comprises the following steps:
[0040] S1. Add 20 g of 1,3-propylene glycol, 15 g of 1,6-hexanediol, 12 g of succinic acid, 15 g of phthalic anhydride, 20 g of maleic anhydride and 0.4 g of monobutyl tin oxide as a catalyst into a reactor, heat and stir to dehydrate at 210° C. in a nitrogen atmosphere, and obtain an unsaturated polyester solution when the acid value of the reaction system drops to 25 mgKOH / g.
[0041] S2. Add 20 g of the composite thermal conductive filler and 35 g of the modified carboxylated styrene butadiene emulsion to 50 g of the unsaturated polyester solution prepared in step S1, stir evenly, then add 12 g of the cross-linking agent epoxidized soybean acrylate, 0.5 g of the initiator benzoyl peroxide and 0.4 g of the accelerator zinc oxide, mix evenly and degas, and cure at 120° C. for 5 h to obtain an unsaturated polyester resin composite material.
[0042] Wherein, the preparation method of the composite thermal conductive filler is as follows:
[0043] (1) 10 g of expanded graphite was immersed in 100 g of a 2 wt % boric acid solution, taken out and dried at 60° C., and then placed in an ammonia atmosphere for calcination, with an ammonia flow rate of 100 mL / min, a calcination temperature of 600° C., and a calcination time of 45 min to obtain an expanded graphite-supported nano-boron nitride material;
[0044] (2) 10 g of expanded graphite-loaded nano-boron nitride material was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of silane coupling agent KH550 was added thereto, stirred for 2 h, filtered, washed, and dried to obtain a composite thermal conductive filler.
[0045] The preparation method of the modified carboxyl styrene butadiene emulsion is as follows:
[0046] (01) 1 g of sodium dodecyl sulfate and 2 g of tert-dodecyl mercaptan were added to 100 g of deionized water, stirred evenly, and then nitrogen was introduced to expel the air. Then, 20 g of butadiene, 20 g of 3,5-bis(trifluoromethyl)styrene, and 10 g of acrylic acid were added thereto. The mixture was stirred and heated to 50° C., and 0.8 g of initiator ammonium persulfate was added. The reaction was allowed to proceed for 3 h. After the reaction was completed, a carboxylated styrene butadiene latex dispersion was obtained.
[0047] (02) 35 g of carboxylated styrene butadiene latex dispersion and 5 g of ethylene glycol diglycidyl ether were mixed evenly, and heated at 85° C. for 2 h to obtain a modified carboxylated styrene butadiene latex.
[0048] Example 2
[0049] A method for preparing an unsaturated polyester resin composite material comprises the following steps:
[0050] S1. Add 15 g of 1,3-propylene glycol, 20 g of 1,6-hexanediol, 10 g of succinic acid, 20 g of phthalic anhydride, 15 g of maleic anhydride and 0.3 g of monobutyl tin oxide as a catalyst into a reactor, heat and stir to dehydrate at 210° C. in a nitrogen atmosphere, and obtain an unsaturated polyester solution when the acid value of the reaction system drops to 25 mgKOH / g.
[0051] S2. Add 15 g of the composite thermal conductive filler and 30 g of the modified carboxylated styrene butadiene emulsion to 40 g of the unsaturated polyester solution prepared in step S1, stir evenly, then add 10 g of the cross-linking agent epoxidized soybean acrylate, 0.4 g of the initiator benzoyl peroxide and 0.3 g of the accelerator barium oxide, mix evenly and degas, and cure at 140° C. for 2 h to obtain an unsaturated polyester resin composite material.
[0052] Wherein, the preparation method of the composite thermal conductive filler is as follows:
[0053] (1) 20 g of expanded graphite was immersed in 150 g of a 2 wt% boric acid solution, taken out and dried at 60° C., and then placed in an ammonia atmosphere for calcination, with an ammonia flow rate of 200 mL / min, a calcination temperature of 450° C., and a calcination time of 60 min to obtain an expanded graphite-supported nano-boron nitride material;
[0054] (2) 15 g of expanded graphite-loaded nano-boron nitride material was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 3 g of silane coupling agent KH550 was added thereto, stirred for 2 h, filtered, washed, and dried to obtain a composite thermal conductive filler.
[0055] The preparation method of the modified carboxyl styrene butadiene emulsion is as follows:
[0056] (01) 2 g of sodium dodecyl sulfate and 3 g of tert-dodecyl mercaptan were added to 100 g of deionized water, stirred evenly, and then nitrogen was introduced to expel the air. Then, 25 g of butadiene, 15 g of 3,5-bis(trifluoromethyl)styrene, and 15 g of acrylic acid were added thereto. The mixture was stirred and heated to 50° C., and 1 g of initiator ammonium persulfate was added. The reaction was allowed to proceed for 3 h. After the reaction was completed, a carboxylated styrene butadiene latex dispersion was obtained.
[0057] (02) 30 g of carboxylated styrene butadiene latex dispersion and 4 g of ethylene glycol diglycidyl ether were mixed evenly, and heated at 70° C. for reaction for 3 h to obtain a modified carboxylated styrene butadiene latex.
[0058] Example 3
[0059] A method for preparing an unsaturated polyester resin composite material comprises the following steps:
[0060] S1. Add 25 g of 1,3-propylene glycol, 10 g of 1,6-hexanediol, 15 g of succinic acid, 15 g of phthalic anhydride, 25 g of maleic anhydride and 0.5 g of monobutyl tin oxide as a catalyst into a reactor, heat and stir to dehydrate at 220° C. in a nitrogen atmosphere, and obtain an unsaturated polyester solution when the acid value of the reaction system drops to 25 mgKOH / g.
[0061] S2. Add 25 g of composite thermal conductive filler and 40 g of modified carboxylated styrene butadiene emulsion to 60 g of the unsaturated polyester solution prepared in step S1, stir evenly, then add 15 g of cross-linking agent epoxidized soybean acrylate, 0.6 g of initiator benzoyl peroxide and 0.5 g of accelerator cobalt cyclohexaneate, mix evenly and degas, and cure at 130° C. for 3 h to obtain an unsaturated polyester resin composite material.
[0062] Wherein, the preparation method of the composite thermal conductive filler is as follows:
[0063] (1) 15 g of expanded graphite was immersed in 150 g of a 2 wt % boric acid solution, taken out and dried at 60° C., and then placed in an ammonia atmosphere for calcination, with an ammonia flow rate of 150 mL / min, a calcination temperature of 500° C., and a calcination time of 50 min to obtain an expanded graphite-supported nano-boron nitride material;
[0064] (2) 12 g of expanded graphite-loaded nano-boron nitride material was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 2 g of silane coupling agent KH550 was added thereto, stirred for 2 h, filtered, washed, and dried to obtain a composite thermal conductive filler.
[0065] The preparation method of the modified carboxyl styrene butadiene emulsion is as follows:
[0066] (01) 2 g of sodium dodecyl sulfate and 2 g of tert-dodecyl mercaptan were added to 100 g of deionized water, stirred evenly, and then nitrogen was introduced to expel the air. Then, 20 g of butadiene, 25 g of 3,5-bis(trifluoromethyl)styrene, and 12 g of acrylic acid were added thereto. The mixture was stirred and heated to 50° C., and 0.5 g of initiator ammonium persulfate was added. The reaction was allowed to proceed for 3 h. After the reaction was completed, a carboxylated styrene butadiene latex dispersion was obtained.
[0067] (02) 40 g of carboxylated styrene butadiene latex dispersion and 6 g of ethylene glycol diglycidyl ether were mixed evenly, and heated at 70° C. for reaction for 3 h to obtain a modified carboxylated styrene butadiene latex.
[0068] Comparative Example 1
[0069] A method for preparing an unsaturated polyester resin composite material comprises the following steps:
[0070] S1. Add 20 g of 1,3-propylene glycol, 15 g of 1,6-hexanediol, 12 g of succinic acid, 15 g of phthalic anhydride, 20 g of maleic anhydride and 0.4 g of monobutyl tin oxide as a catalyst into a reactor, heat and stir to dehydrate at 210° C. in a nitrogen atmosphere, and obtain an unsaturated polyester solution when the acid value of the reaction system drops to 25 mgKOH / g.
[0071] S2. Add 20 g of thermal conductive filler and 35 g of modified carboxylated styrene butadiene emulsion to 50 g of the unsaturated polyester solution prepared in step S1, stir evenly, then add 12 g of cross-linking agent epoxidized soybean acrylate, 0.5 g of initiator benzoyl peroxide and 0.4 g of accelerator zinc oxide, mix evenly and degas, and cure at 120° C. for 5 h to obtain an unsaturated polyester resin composite material.
[0072] Wherein, the preparation method of the thermal conductive filler is as follows:
[0073] 10 g of expanded graphite was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of silane coupling agent KH550 was added thereto, stirred for 2 h, filtered, washed, and dried to obtain a thermal conductive filler.
[0074] The preparation method of the modified carboxyl styrene butadiene emulsion is as follows:
[0075] (01) 1 g of sodium dodecyl sulfate and 2 g of tert-dodecyl mercaptan were added to 100 g of deionized water, stirred evenly, and then nitrogen was introduced to expel the air. Then, 20 g of butadiene, 20 g of 3,5-bis(trifluoromethyl)styrene, and 10 g of acrylic acid were added thereto. The mixture was stirred and heated to 50° C., and 0.8 g of initiator ammonium persulfate was added. The reaction was allowed to proceed for 3 h. After the reaction was completed, a carboxylated styrene butadiene latex dispersion was obtained.
[0076] (02) 35 g of carboxylated styrene butadiene latex dispersion and 5 g of ethylene glycol diglycidyl ether were mixed evenly, and heated at 85° C. for 2 h to obtain a modified carboxylated styrene butadiene latex.
[0077] Compared with Example 1, in Comparative Example 1, the expanded graphite was not treated with loading nano-boron nitride.
[0078] Comparative Example 2
[0079] A method for preparing an unsaturated polyester resin composite material comprises the following steps:
[0080] S1. Add 20 g of 1,3-propylene glycol, 15 g of 1,6-hexanediol, 12 g of succinic acid, 15 g of phthalic anhydride, 20 g of maleic anhydride and 0.4 g of monobutyl tin oxide as a catalyst into a reactor, heat and stir to dehydrate at 210° C. in a nitrogen atmosphere, and obtain an unsaturated polyester solution when the acid value of the reaction system drops to 25 mgKOH / g.
[0081] S2. Add 20 g of the composite thermal conductive filler and 35 g of the modified carboxylated styrene butadiene emulsion to 50 g of the unsaturated polyester solution prepared in step S1, stir evenly, then add 12 g of the cross-linking agent epoxidized soybean acrylate, 0.5 g of the initiator benzoyl peroxide and 0.4 g of the accelerator zinc oxide, mix evenly and degas, and cure at 120° C. for 5 h to obtain an unsaturated polyester resin composite material.
[0082] Wherein, the preparation method of the composite thermal conductive filler is as follows:
[0083] (1) 10 g of expanded graphite was immersed in 100 g of a 2 wt % boric acid solution, taken out and dried at 60° C., and then placed in an ammonia atmosphere for calcination, with an ammonia flow rate of 100 mL / min, a calcination temperature of 600° C., and a calcination time of 45 min to obtain an expanded graphite-supported nano-boron nitride material;
[0084] (2) 10 g of expanded graphite-loaded nano-boron nitride material was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of silane coupling agent KH550 was added thereto, stirred for 2 h, filtered, washed, and dried to obtain a composite thermal conductive filler.
[0085] The preparation method of the modified carboxyl styrene butadiene emulsion is as follows:
[0086] Add 1g of sodium dodecyl sulfate and 2g of tert-dodecyl mercaptan to 100g of deionized water, stir evenly, then introduce nitrogen to expel the air, then add 20g of butadiene, 20g of 3,5-bis(trifluoromethyl)styrene, and 10g of acrylic acid, stir and heat to 50°C, add 0.8g of initiator ammonium persulfate, react for 3h, and after the reaction is completed, a modified carboxylated butadiene styrene emulsion is obtained.
[0087] Compared with Example 1, Comparative Example 2 does not use ethylene glycol diglycidyl ether to treat the carboxylated styrene butadiene latex dispersion.
[0088] Comparative Example 3
[0089] A method for preparing an unsaturated polyester resin composite material comprises the following steps:
[0090] S1. Add 20 g of 1,3-propylene glycol, 15 g of 1,6-hexanediol, 12 g of succinic acid, 15 g of phthalic anhydride, 20 g of maleic anhydride and 0.4 g of monobutyl tin oxide as a catalyst into a reactor, heat and stir to dehydrate at 210° C. in a nitrogen atmosphere, and obtain an unsaturated polyester solution when the acid value of the reaction system drops to 25 mgKOH / g.
[0091] S2. Add 20 g of the composite thermal conductive filler and 35 g of the modified carboxylated styrene butadiene emulsion to 50 g of the unsaturated polyester solution prepared in step S1, stir evenly, then add 12 g of the cross-linking agent epoxidized soybean acrylate, 0.5 g of the initiator benzoyl peroxide and 0.4 g of the accelerator zinc oxide, mix evenly and degas, and cure at 120° C. for 5 h to obtain an unsaturated polyester resin composite material.
[0092] Wherein, the preparation method of the composite thermal conductive filler is as follows:
[0093] (1) 10 g of expanded graphite was immersed in 100 g of a 2 wt % boric acid solution, taken out and dried at 60° C., and then placed in an ammonia atmosphere for calcination, with an ammonia flow rate of 100 mL / min, a calcination temperature of 600° C., and a calcination time of 45 min to obtain an expanded graphite-supported nano-boron nitride material;
[0094] (2) 10 g of expanded graphite-loaded nano-boron nitride material was dispersed in 100 mL of 80 wt% ethanol aqueous solution, and then 1 g of silane coupling agent KH550 was added thereto, stirred for 2 h, filtered, washed, and dried to obtain a composite thermal conductive filler.
[0095] The preparation method of the modified carboxyl styrene butadiene emulsion is as follows:
[0096] (01) 1 g of sodium dodecyl sulfate and 2 g of tert-dodecyl mercaptan were added to 100 g of deionized water, stirred evenly, and then nitrogen was introduced to expel the air. Then, 20 g of butadiene, 20 g of styrene, and 10 g of acrylic acid were added thereto, and the temperature was raised to 50° C. with stirring, and 0.8 g of initiator ammonium persulfate was added. The reaction was allowed to proceed for 3 h. After the reaction was completed, a carboxylated styrene butadiene latex dispersion was obtained;
[0097] (02) 35 g of carboxylated styrene butadiene latex dispersion and 5 g of ethylene glycol diglycidyl ether were mixed evenly, and heated at 85° C. for 2 h to obtain a modified carboxylated styrene butadiene latex.
[0098] Compared with Example 1, Comparative Example 3 uses styrene to replace 3,5-bis(trifluoromethyl)styrene.
[0099] The properties of the unsaturated polyester resin composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested as follows:
[0100] Tensile strength and tensile elongation at break: According to ASTM D638, the unsaturated polyester resin composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were respectively made into specimens with a size of 20 mm×4 mm×3 mm. The tensile strength and tensile elongation at break of the specimens were tested at a tensile rate of 0.5 mm / min at 25° C. Each group of specimens was tested three times, and the results were averaged.
[0101] Thermal conductivity: The thermal conductivity of the prepared samples was tested using a German NETZSCH laser flash thermal conductivity meter LFA-447. The sample size was 50mm×50mm×2mm. Each group of samples was measured three times and the results were averaged.
[0102] Limiting oxygen index test: Test according to ISO 4589-2, test each set of samples three times and take the average value of the results;
[0103] The test results are shown in Table 1 below:
[0104] Table 1
[0105]
[0106] Chemical stability test: According to ASTM D638 standard, the unsaturated polyester resin composite materials provided in Example 1 and Comparative Examples 1-3 were made into samples with a size of 20 mm×4 mm×3 mm, and each group of samples was placed in the following various environments for treatment, and then the tensile strength retention rate after treatment was tested. Each group of samples was tested three times, and the results were averaged.
[0107] Environment 1: 5 cm from the UV lamp with an irradiation intensity of 200 μW / cm 2 Place in ultraviolet environment for 7 days;
[0108] Environment 2: Place in an environment with a temperature of 85°C and a relative humidity of 90% for 7 days;
[0109] Environment 3: Soaked in 500 mL of 5 wt% sodium hydroxide solution for 1 day;
[0110] The test results are shown in Table 2:
[0111] Table 2
[0112]
[0113] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A method for preparing an unsaturated polyester resin composite material, characterized in that: The steps include: S1, adding 1,3-propylene glycol, 1,6-hexanediol, succinic acid, phthalic anhydride, maleic anhydride and catalyst monobutyl tin oxide into a reactor, heating and stirring at 190-220° C. in an inert atmosphere for dehydration reaction, and obtaining an unsaturated polyester solution when the acid value of the reaction system drops to 25-30 mgKOH / g; S2, adding the composite thermal conductive filler and the modified carboxyl styrene butadiene emulsion to the unsaturated polyester solution prepared in step S1, stirring evenly, then adding the crosslinking agent, initiator and accelerator, mixing evenly and degassing, and curing at 120-140° C. for 2-5 hours to obtain an unsaturated polyester resin composite material; The preparation method of the composite thermal conductive filler is as follows: (1) immersing the expanded graphite in a boric acid solution, taking it out and drying it, and then placing it in an ammonia atmosphere for calcining to obtain an expanded graphite-loaded nano-boron nitride material; (2) dispersing the expanded graphite-loaded nano-boron nitride material in an ethanol aqueous solution, then adding a silane coupling agent KH550 thereto, stirring for 1-3 hours, filtering, washing, and drying to obtain a composite thermal conductive filler; The preparation method of the modified carboxyl styrene butadiene emulsion is as follows: (01) adding sodium dodecyl sulfate and tert-dodecyl mercaptan to deionized water, stirring evenly, then introducing nitrogen to expel the air, then adding butadiene, 3,5-bis(trifluoromethyl)styrene, and acrylic acid, stirring and heating to 45-55° C., adding initiator ammonium persulfate, reacting for 2-5 hours, and after the reaction is completed, obtaining a carboxylated styrene butadiene latex dispersion; (02) The carboxylated styrene butadiene latex dispersion and ethylene glycol diglycidyl ether are uniformly mixed, and heated at 70-85° C. for reaction for 2-3 hours to obtain a modified carboxylated styrene butadiene latex.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of 1,3-propylene glycol, 1,6-hexanediol, succinic acid, phthalic anhydride, maleic anhydride and monobutyl tin oxide is 15-25:10-20:10-15:10-20:15-25:0.3-0.
5.
3. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the unsaturated polyester solution, the composite thermal conductive filler, the modified carboxylated styrene butadiene emulsion, the crosslinking agent, the initiator and the accelerator is 40-60:15-25:30-40:10-15:0.4-0.6:0.3-0.
5.
4. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of expanded graphite to boric acid solution is 1-2:10-15, and the mass fraction of boric acid solution is 1-3%.
5. The preparation method according to claim 1, characterized in that: In step (1), the calcination process conditions are: the flow rate of ammonia is 100-200 mL / min, the calcination temperature is 450-600° C., and the calcination time is 45-60 min.
6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the expanded graphite-loaded nano-boron nitride material to the silane coupling agent KH550 is 10-15:1-3.
7. The preparation method according to claim 1, characterized in that: In step (01), the mass ratio of sodium dodecyl sulfate, tert-dodecyl mercaptan, deionized water, butadiene, 3,5-bis(trifluoromethyl)styrene, acrylic acid and ammonium persulfate is 1-2:1-3:100:20-25:15-25:10-15:0.5-1.
8. The preparation method according to claim 1, characterized in that: In step (02), the mass ratio of carboxylated styrene butadiene latex dispersion to ethylene glycol diglycidyl ether is 30-40:4-6.
9. The preparation method according to claim 1, characterized in that: In step S2, the crosslinking agent is selected from epoxidized soybean oil acrylate, the initiator is selected from benzoyl peroxide, ethyl perbenzoate or dicumyl peroxide, and the accelerator is selected from cobalt naphthenate, zinc oxide or barium oxide.
10. The unsaturated polyester resin composite material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Modified unsaturated polyester resin and preparation method thereof
CN108084419A
Composite heat-dissipation material for semiconductor and preparation method thereof
CN111040324A
Anisotropic composite material and preparation method thereof
CN115491009A